The Modern Leviathan!! - (:unkn) unknown (Fores, S. W., 1796)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820; Burke, Edmund, 1729-1797?